Fluoroquinolone Use Is a Risk Factor for Methicillin-Resistant Staphylococcus aureus Acquisition in Long-term Care Facilities: A Nested Case-Case-Control Study. (11th April 2014) - Couderc, Clotilde; Jolivet, Sarah; Thiébaut, Anne C. M.; Ligier, Caroline; Remy, Laetitia; Alvarez, Anne-Sophie; Lawrence, Christine; Salomon, Jérôme; Herrmann, Jean-Louis; Guillemot, Didier; ,
Abstract : A case-case-control analysis of risk factors for acquisition of methicillin-resistant Staphylococcus aureus (MRSA) risk factors in long-term care facilities found fluoroquinolones to be independently and significantly associated with MRSA acquisition, suggesting that control measures to limit MRSA spread should also be based on optimization of fluoroquinolone use. Abstract : Background.  Methicillin-resistant Staphylococcus aureus (MRSA) nasal colonization is a well-established risk factor for subsequent infection and a key event in interindividual transmission. Some studies have showed an association between fluoroquinolones and MRSA colonization or infection. The present study was performed to identify specific risk factors for MRSA acquisition in long-term care facilities (LTCFs). Methods.  A prospective cohort of patients naive for S. aureus colonization was established and followed (January 2008 through October 2010) in 4 French LTCFs. Nasal colonization status and potential risk factors were assessed weekly for 13 weeks after inclusion. Variables associated with S. aureus acquisition were identified in a nested-matched case-case-control study using conditional logistic regression models. Cases were patients who acquired MRSA (or methicillin-sensitive S. aureus [MSSA]). Patients whose nasal swab samples were always negative served as controls. Matching criteria were center, date of first nasal swab sample, and exposure time. Results.  Among 451 included patients, 76 MRSA cases were matched to 207 controls and 112 MSSA cases to 208 controls. Multivariable analysis retained fluoroquinolones (odds ratio, 2.17; 95% confidence interval, 1.01–4.67), male sex (2.09; 1.10–3.98), and more intensive care at admission (3.24; 1.74–6.04) as significantly associated with MRSA acquisition, and body-washing assistance (2.85; 1.27–6.42) and use of a urination device (1.79; 1.01–3.18) as significantly associated with MSSA acquisition. Conclusions.  Our results suggest that fluoroquinolones are a risk factor for MRSA acquisition. Control measures to limit MRSA spread in LTCFs should also be based on optimization of fluoroquinolone use.